PENTINGNYA PEMAHAMAN BAHASA INDONESIA DALAM MENGUKUR KEMAMPUAN AKADEMIK PADA SUBTES UTBK - Dinda Nabila Marchanigia; Ifta Khotimatuz Zahro; Gardhena Olivia Ramadhani Putri Basori; Mohamad Catur Fajar Prastio; Muhammad Abduh Azhary; Eni Nurhayati (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This research aims to determine the effect of understanding Indonesian on students' academic abilities, especially in the Computer Based Writing Examination (UTBK) subtest which focuses on reading comprehension and literacy. Considering the important role of Indonesian in the teaching and learning process and academic assessment, this research identifies the extent to which language mastery influences students' ability to analyze information and answer questions correctly. Using a qualitative descriptive study method with a Google Form questionnaire, this research was conducted on new students at the National Development University